Improvement of chicken plasma protein hydrolysate angiotensin I‐converting enzyme inhibitory activity by optimizing plastein reaction. Issue 6 (18th May 2020) - Gao, Dandan; Guo, Penghui; Cao, Xin; Ge, Lili; Ma, Hongxin; Cheng, Hao; Ke, Yiqiang; Chen, Shien; Ding, Gongtao; Feng, Ruofei; Qiao, Zilin; Bai, Jialin; et al.
Abstract: Chicken plasma protein hydrolysate (CPPH) was prepared by trypsin with angiotensin I‐converting enzyme (ACE) inhibitory activity of 53.5% ± 0.14% and the degree of hydrolysis (DH) of 16.22% ± 0.21% at 1 mg·ml −1 ; then, five proteases, including pepsin, trypsin, papain, alcalase, and neutrase, were employed to improve ACE inhibitory ability by catalyzing plastein reaction. The results indicated that trypsin‐catalyzed plastein reaction showed the highest ACE inhibitory activity. The exogenous amino acids of leucine, histidine, tyrosine, valine, and cysteine were selected to modify the CPPH. The leucine‐modified plastein reaction released the highest ACE inhibitory activity. The effects of four reaction parameters on plastein reaction were studied, and the optimal conditions with the purpose of obtaining the most powerful ACE inhibitory peptides from modified products were obtained by response surface methodology (RSM). The maximum ACE inhibition rate of the modified hydrolysate reached 82.07% ± 0.03% prepared at concentration of hydrolysates of 30%, reaction time of 4.9 hr, pH value of 8.0, temperature of 40°C, and E/S ratio of 5, 681.62 U·g −1 . The results indicated that trypsin‐catalyzed plastein reaction increased ACE inhibitory activity of chicken plasma protein hydrolysates by 28.57%. Abstract : Chicken plasma protein was hydrolyzed by trypsin to obtain CPPH with ACE inhibitory activity, and the hydrolysates were modified by a trypsin‐catalyzed plastein reaction to improve its ACE inhibitory activity. The reaction conditions of trypsin‐catalyzed plastein reaction of CPPH were optimized by single‐factor experiments and response surface methodology, obtaining optimal condition for improving ACE inhibitory activity. The result showed that the trypsin‐catalyzed plastein reaction of CPPH could enhance ACE inhibitory activity of modified hydrolysates, indicating that chicken plasma protein has the potential in the development of new functional foods.